SCRUB TYPHUS – THE DANGER OF BEING UNDETECTED: LABORATORY INVESTIGATIONS AND CONTEMPORARY INFECTIONS - PRASANNA VENKATESH S; ANUPRIYA A (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: To identify scrub typhus cases among acute undifferentiated febrile illness (AUFI) by laboratory investigations. To determine the efficacy of immunoglobulin M-enzyme-linked immunosorbent assay (IgM-ELISA) in detecting the cases of scrub typhus and to compare the Weil–Felix test, rapid test, and IgM-ELISA for the diagnosis of scrub typhus. Methods: A total of 110 AUFI cases participated (65 from rural, 16 from semi-urban, and 29 from urban setups; 33 farmers, 15 animal rearing workers, nine drivers, 19 laborers, and 34 other jobs). Blood was collected after due explanation and consent. Results: The Weil–Felix test tested 22 samples as positive, whereas the rapid card test, IgM-ELISA, and polymerase chain reaction detected 15 samples as positive for infection. The sensitivity and specificity of the Weil–Felix test were 66.67% and 87.36%, respectively. The sensitivity and specificity of the rapid card test and IgM-ELISA were 100%. There were coinfections with Leptospira, typhoid, and COVID-19. Conclusion: Laboratory investigations revealed the various organ systems the disease could affect and that it could serve to determine the prognosis. The use of rapid card tests is on par with IgM-ELISA, making it a suitable candidate for diagnosing in remote setups.